Kondisi Sumur Gali Dan Kandungan Bakteri Escherichia Coli Pada Air Sumur Gali Di Desa Bokonusan Kecamatan Semau Kabupaten Kupang Tahun 2017 - Albina Bare Telan; Agustina Agustina; Dison Baok (JURNAL INFO KESEHATAN, 2017)
The availability of clean water facilities must meet the quantity and quality requirements of the availability of sufficient number of clean water facilities for the population in accordance with the number of people or public Permenkes RI No.416 / MENKES / PER / 1X / 1990 on the terms and quality of clean water that stipulates the amount Escherichia coli in clean water is 0, / 100 ml samples of Escherichia coli bacteria are selected as sanitary indicators because the bacteria Escherichia coli is a normal flora present in the human intestines and intestines of warm-blooded animals. The purpose of this study was to measure the distance of dug wells with pollutant sources, to assess the risk of dug well contamination, to assess the physical construction of dug wells (digging well lips, digging well wall, digging well floor, and SPAL, knowing bacteriological quality (E. coli) in Bokonusan Village Semau Subdistrict of Kab Kupang Year 2017. The type of research used is descriptive research with sample size as many as 8 samples of dug wells in Bokonusan Village Semau Subdistrict, Kupang District in 2017 (Notoatmodjo, 2002). The results showed that from 8 dug wells inspected, it was found that the dug well with the pollutant source did not fulfill the requirement of 87.5% and the category was 12.5%, the level of the pollutant dug well was 75%, the risk was low 25% Construction of dug well on 50% excavation lips 50% unqualified, well floor 62% unqualified, well dug wall well 50% not eligible, SPAL well dug 100% not qualified and examination results of E. coli content on 6 well water dug obtained results 100% containing that does not meet E. coli (100%). The conclusion of this research is that the average distance of dug well from pollutant source is <11 meters, with a medium risk level, the dug well construction is not eligible and there are 6 digging wells containing E. coli, so it is suggested to the community to improve the physical condition of the well dig like well lips, well floor, well wall, and sewerage (SPAL) and always consume drinking water that has been cooked to boil.